NSC30049 inhibits Chk1 pathway in 5-FU-resistant CRC bulk and stem cell populations - Narayan, Satya (Oncotarget, 2017)
The 5-fluorouracil (5-FU) treatment induces DNA damage and stalling of DNA replication forks. These stalled replication forks then collapse to form one sided double-strand breaks, leading to apoptosis. However, colorectal cancer (CRC) stem cells rapidly repair the stalled/collapsed replication forks and overcome treatment effects. Recent evidence suggests a critical role of checkpoint kinase 1 (Chk1) in preventing the replicative stress. Therefore, Chk1 kinase has been a target for developing mono or combination therapeutic agents. In the present study, we have identified a novel orphan molecule NSC30049 (NSC49L) that is effective alone, and in combination potentiates 5-FU-mediated growth inhibition of CRC heterogeneous bulk and FOLFOX-resistant cell lines in culture with minimal effect on normal colonic epithelial cells. It also inhibits the sphere forming activity of CRC stem cells, and decreases the expression levels of mRNAs of CRC stem cell marker genes. Results showed that NSC49L induces 5-FU-mediated S-phase cell cycle arrest due to increased load of DNA damage and increased γ-H2AX staining as a mechanism of cytotoxicity. The pharmacokinetic analysis showed a higher bioavailability of this compound, however, with a short plasma half-life. The drug is highly tolerated by animals with no pathological aberrations. Furthermore, NSC49L showed very potent activity in a HDTX model of CRC stem cell tumors either alone or in combination with 5-FU. Thus, NSC49L as a single agent or combined with 5-FU can be developed as a therapeutic agent by targeting the Chk1 pathway in 5-FU-resistant CRC heterogeneous bulk and CRC stem cell populations.